Intention to use contraceptives in Jordan: Further analysis of the Jordan population and family health survey 2017-18 - Riese, Sara (DHS Further Analysis Reports No. 141, 2020)
Intention to use contraception in the future among women in Jordan has decreased over the past 30 years. To better understand the determinants of contraceptive intention, this study uses the theory of planned behavior to identify attitudes, social norms, perceived behavioral control, and sociodemographic factors associated with contraceptive intention. We use data from 5,789 currently married, fecund women not currently using contraception from the most recent Jordan Population and Family Health Survey and estimate logistic regression models for contraceptive intention. Over 60% of women in our sample do not intend to use contraception in the future. In multivariate analysis, variables related to all three components of the theory of planned behavior were significantly associated with contraceptive intention. Women who are undecided about having more children had lower odds of intending to use contraception compared to women who want no more children. Compared with women who wanted no children, women who want one to four children had higher odds of contraceptive intention. Women who do not know how many children their husband desires have lower odds of intending to use contraception compared to women who want the same number of children as their husbands. Women who have used contraceptives have over three times the odds of intending to use contraception in the future compared to women who have not. Joint decision making for contraceptive nonuse is associated with higher odds of contraceptive intention compared to a woman making the decision alone. Increasing age is associated with lower odds of contraceptive intention compared to younger age. Women whose husbands have higher levels of education have higher odds of intending to use contraception compared to those with husbands with no education. Compared with women who are not currently working, women who work have lower odds of contraceptive intention. Odds of intending to use contraception in the future varied in different governorates with women in Ajloun having over two times the odds of intending to use contraception, and women in Karak over 50% lower odds, compared to women in Amman. These findings suggest that investment in demand-side interventions that promote contraceptive use through shifting social norms on gender and addressing common concerns about contraceptive use are warranted. Targeting specific groups by age and previous contraceptive use may also allow for focused messaging that addresses unique barriers within these groups.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This report presents findings from a further analysis of the 2017-18 Jordan Population and Family Health Survey (JPFHS). This report is a publication of The DHS Program which collects, analyzes, and disseminates data on fertility, family planning, maternal and child health, nutrition, and HIV/AIDS. Funding was provided by the U.S. Agency for International Development (USAID) through the DHS Program (#720-0AA-18C-00083). The opinions expressed here are those of the authors and do not necessarily reflect the views of USAID and other cooperating agencies.